Analisis Pola Perilaku Penelusuran Informasi di Kalangan Mahasiswa UINSU - Tengku Riyan Hidayat; Risky Mulyadi; Franindya Purwaningtyas (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
Information seeking behavior is reviewed from the theory of David Ellis 1989 with six forming elements, then refined by Meho and Tibbo in 2003 with ten forming elements of information seeking behavior sequentially namely starting, chaining, browsing, monitoring, accessing, differentiating, extracting , verifying, networking and information managing. This study uses qualitative research with field research. Qualitative research is research that does not use calculations. This qualitative research emphasizes the meaning, reasoning, definition of certain situations (in certain contexts). The qualitative approach is more about the process than the end result. This study resulted that overall the informants agreed to carry out information search activities when they received assignments from their lecturers. In carrying out the information search process, they tend to use electronic sources rather than printed sources. The reason for using electronic sources (Google) in finding information is that it is easy and fast so that when compared to printed sources, they have to go to the library first if the collection of books at home is insufficient. Keywords: Film Search, Information Search, Information Needs